Pendampingan Pengelolaan Sampah di Pondok Pesantren Islam Ulul Albab Menuju Zero Waste Boarding School: Waste Management Assistance at Ulul Albab Islamic Boarding School Towards Zero Waste Boarding School - Soesiladi Esti Widodo; Setyo Widagdo; Zulferiyenni Zulferiyenni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
One of the common problems that can be easily found in educational institutions in general, and Islamic boarding schools in particular, is the poor handling of organic and inorganic waste. If waste is handled correctly, it will not only minimize environmental pollution but can also be a source of fundraising. Ulul Albab Islamic Boarding School (UA IBS), which is located in the village of Banjaragung, dist. Jatiagung, reg. South Lampung, Lampung province, Indonesia, was the target partner in organic and inorganic waste management assistance activities. This initial assistance activity, in the form of counseling, was the initial part of the Assistance Program for Organic and Inorganic Waste Management at UA IBS. The main objective of this extension activity was to increase the knowledge of UA IBS managers and residents about integrated organic and inorganic waste management. The method of carrying out this activity was a face-to-face discussion on the concept and technique of integrated waste management to produce a value-added product in the form of compost. The results of this counseling activity were evident from the response of the manager, asatidzah, and students who enthusiastically participated in the activity and increased their knowledge about integrated organic and inorganic waste management to become value-added products.